If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7x-2)=8-4x
We move all terms to the left:
(7x-2)-(8-4x)=0
We add all the numbers together, and all the variables
(7x-2)-(-4x+8)=0
We get rid of parentheses
7x+4x-2-8=0
We add all the numbers together, and all the variables
11x-10=0
We move all terms containing x to the left, all other terms to the right
11x=10
x=10/11
x=10/11
| x3x=−2 | | 5a-3=52 | | x8x=27 | | #x8x=27 | | 9-3x=235x | | 3x+5=2×-3 | | 2x+31+3x+34=90 | | T=3n+10 | | 10-250x^2=0 | | X=20,y=20 | | (0.8+x)(x-4)=0 | | 4(2a+5)=100 | | xx+3=−8 | | a)6a+10=3a-14 | | c=((2+3)/6)/3 | | 1+3x=-1+5x | | xx+3=8 | | (√7)^(2x+6)-1=0 | | 590p+180=3200 | | (√7)^2x+6-1=0 | | 3x+27=6x+30 | | 14x^=7x | | 3.2=(x+45) | | 4^-2x=128 | | 10x=4+9 | | 5s+36=171 | | a/6=7/3 | | 5×+3y=40 | | (x+2)+2x=5(2x-5)-x | | 5p =3p +8 | | 2x+12=14=17-3x | | x2-30x-264=0 |